6(u-9)-1=-5(-3u+8)-3u

Simple and best practice solution for 6(u-9)-1=-5(-3u+8)-3u equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(u-9)-1=-5(-3u+8)-3u equation:


Simplifying
6(u + -9) + -1 = -5(-3u + 8) + -3u

Reorder the terms:
6(-9 + u) + -1 = -5(-3u + 8) + -3u
(-9 * 6 + u * 6) + -1 = -5(-3u + 8) + -3u
(-54 + 6u) + -1 = -5(-3u + 8) + -3u

Reorder the terms:
-54 + -1 + 6u = -5(-3u + 8) + -3u

Combine like terms: -54 + -1 = -55
-55 + 6u = -5(-3u + 8) + -3u

Reorder the terms:
-55 + 6u = -5(8 + -3u) + -3u
-55 + 6u = (8 * -5 + -3u * -5) + -3u
-55 + 6u = (-40 + 15u) + -3u

Combine like terms: 15u + -3u = 12u
-55 + 6u = -40 + 12u

Solving
-55 + 6u = -40 + 12u

Solving for variable 'u'.

Move all terms containing u to the left, all other terms to the right.

Add '-12u' to each side of the equation.
-55 + 6u + -12u = -40 + 12u + -12u

Combine like terms: 6u + -12u = -6u
-55 + -6u = -40 + 12u + -12u

Combine like terms: 12u + -12u = 0
-55 + -6u = -40 + 0
-55 + -6u = -40

Add '55' to each side of the equation.
-55 + 55 + -6u = -40 + 55

Combine like terms: -55 + 55 = 0
0 + -6u = -40 + 55
-6u = -40 + 55

Combine like terms: -40 + 55 = 15
-6u = 15

Divide each side by '-6'.
u = -2.5

Simplifying
u = -2.5

See similar equations:

| 5+(9+18-3)-3= | | 7(m+5)=22 | | 8-n=34 | | 7nsquared+7=12n | | 2(4x+3)+6= | | -56=88-9x | | 29-7x=28x-28 | | 9+14x+5x=180 | | 7-2f=1.98 | | 10-2y+4x=0 | | -7[4+7(-5+7)]+16= | | 50+3b=134 | | 3(1)=3 | | 7x+6=2z+2 | | 12x-13=-6x | | 6a-9-8a+5a= | | 5x+200=3x-300 | | -23n+13n+47-5n=-28 | | 3l+4-4l=-3 | | 53+18w=c | | 7x-4=37 | | 3(t-3)-2t=-30 | | (2m+3t)(3m-4t)= | | y=6000(1+0.04)5 | | 9x-8=8x+1 | | x^3-13x^2-2x+26=0 | | 7-3x-(-5x+2)+1+7x=5x | | 2x+4x-9x+7= | | 5(20x+25)=925 | | 10*xy+90=72x | | 12y-5y-7+4= | | 10x-50=7x+1 |

Equations solver categories